2006
DOI: 10.1007/s00439-006-0133-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of transmission ratio distortion of DLG5 R30Q variant in general and implication of an association with Crohn disease in men

Abstract: Recently, we described the association of genetic variation in the discs large homolog 5 (DLG5) gene with inflammatory bowel disease (IBD) in a large European study sample (Stoll et al. in Nat Genet 36:476-480, 2004). Here, we report that the R30Q variant constitutes a susceptibility factor for Crohn disease (CD) in men [odds ratio (OR)=2.49, 95% confidence interval (CI) 1.53-4.06, P<0.001] but not women (OR=1.01, 95% CI=0.70-1.45, P=0.979) using multivariate logistic regression analyses in a unified study sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
3
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 28 publications
(30 reference statements)
3
44
3
1
Order By: Relevance
“…We found several coincidences that are worth mentioning: for instance, DLG5, which is necessary for the polarization of citron kinase in mitotic neural precursors (Chang et al 2010). This locus is associated with Crohn's disease and the susceptibility allele is transmission distorted among male progeny (Friedrichs et al 2006). Another relevant gene is MEGF9 that might have Table 3 Gene ontology enrichment analysis of the regions with highly significant transmission ratio distortion signals (Bayes factor > 100), obtained with the Cytoscape plugin BiNGO (Maere et al 2005) and DAVID tools (Huang et al 2009 a tumor suppressor function and showed a TRD pattern in human pedigrees from the Framingham Heart Study (Paterson et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…We found several coincidences that are worth mentioning: for instance, DLG5, which is necessary for the polarization of citron kinase in mitotic neural precursors (Chang et al 2010). This locus is associated with Crohn's disease and the susceptibility allele is transmission distorted among male progeny (Friedrichs et al 2006). Another relevant gene is MEGF9 that might have Table 3 Gene ontology enrichment analysis of the regions with highly significant transmission ratio distortion signals (Bayes factor > 100), obtained with the Cytoscape plugin BiNGO (Maere et al 2005) and DAVID tools (Huang et al 2009 a tumor suppressor function and showed a TRD pattern in human pedigrees from the Framingham Heart Study (Paterson et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Stoll et al, [12] identified an IBD risk-associated DLG5 haplotype D that is uniquely distinguished by the 113A variant of R30Q. The association of R30Q with IBD has been replicated in other studies from several different patient populations [24][25][26]. Friedrichs et al, found a male-specific association of the R30Q variant with CD, with no association of the R30Q variant with women, nor with the entire sample of men and women [27].…”
Section: Introductionmentioning
confidence: 94%
“…Present approaches have not been able to discern whether these other genes or the class Ⅱ genes are the true risk genes in the HLA locus. [79][80][81][82] , multiple polymorphisms in the MDR1/ABCB1 gene on chromosome 7q [83][84][85][86][87][88][89][90][91][92] , and polymorphisms in the DLG5 gene on chromosome 10q [70,[93][94][95][96][97][98][99][100][101][102] . (See section C.4.1.)…”
Section: Hla Associationsmentioning
confidence: 99%